Analisis pemungutan pajak bumi dan bangunan perdesaan dan perkotaan terhadap pendapatan asli daerah di Kabupaten Klaten - Tri Nur Rohmah; Anastasia Luruk Nahak; Iwan Budiherwanto; Susianti Susianti; Annida Khoiriani (Konsentrasi Pembangunan Regional dan Publik, Prodi Ekonomi Pembangunan, Fakultas Ekonomi dan Bisnis, Universitas Jambi, 2022)
Land and Building Tax Rural and Urban sector (PBB-P2) is a source of regional own-source revenue from the local tax sector, whose management has been transferred to the local government since 2013. Some regions have made it a potential source of local revenue, or even a reliable source of income. PBB-P2 in districts is one that has a positive trend in its realization because it always increases from year to year. This study aims to analyze the effectiveness of PBB-P2 collection and see its contribution to local taxes and Local Revenue in Klaten Regency in the 2016-2020 period. The research method is to use a descriptive quantitative approach and analysis of effectiveness and contribution analysis. The results of the study show that the trend of realization of PBB-P2 revenues is always increasing, while the average level of effectiveness is very effective except for 2019 (effective). PBB-P2’s contribution to regional taxes and PAD is very significant. Increasing the achievement of PBB-P2 can be done by increasing socialization and educating the public regarding the importance of taxes for development and validating turnover data in the SPTPD (Regional Tax Notification Letter) so that no potential is overlooked.